Analisis Kurikulum Terhadap Daya Matematik - Margana (Department of Mathematics Education Program IPI Garut, 2012)
Thinking is one human trait. Since can perceive, people begin to think, and this process continues until the end of his life. Attitude and way of thinking can be developed through a process of learning mathematics because mathematics has a structure and a strong and clear linkages intracompany so anyone who thinks rationally skilled study. Therefore, learning how mathematics can be implemented so as to cultivate students' mathematical power. Mathematics curriculum should be designed not only for students continuing on to higher education but also for entering the job market. Focus of the curriculum can be examined from three aspects, namely Intended Curriculum, Curriculum Implemented and Attained Curriculum. Learning process must be conducted in accordance with the class learning objectives to be achieved. Also, it can also refer to the implementation of the curriculum in other countries.